Maritime Supply Chain Security in the Indo-Pacific Region: Threats and Policy Implications for National Security and Resilience - Nguyen, Hong-Oanh; Van Balen, Michael; Ingram, Aaron; Hurd, Stephen; Chheetri, Prem; Thai, Vinh; Warren, Matthew; Booi, Kam; Oloruntoba, Richard (2022)
By volume, about 99% of Australia’s trade is carried by sea mainly through the Indo-Pacific region. Australia currently imports 90% of liquid fuel from other countries, primarily Japan, Korea and Singapore. Global shipping trade valued around USD3.37 trillion is also passed through the South China Sea, where Strait of Malacca is one of the busiest oil/energy shipping routes in the world. The region especially the South China Sea and East China Sea is subject to increasing maritime security threats due to territorial disputes and the risk of military conflicts. This report presents emerging security challenges facing maritime supply chains in the Indo-Pacific region and the implications for Australia. The report comprises four component studies. The first study is a scenario analysis of maritime security threats in the South China Sea and the broader Indo-Pacific that are associated with three contexts, South China Sea conflict, cyber attack on Australian maritime information systems, and Indo-Pacific maritime logistics network disruption. The result of the scenario analysis indicates that South China Sea conflicts would cause shipping capacity shortage, port operations breakdown, production disruption, technology failures, international armed conflicts, trade sanctions/embargo and diversion. These will likely result in an economic downturn, critical supplies, maritime supply chain disruptions, and increasing military activities in the region. Cyber attacks on Australian maritime information systems will cause navigation operations disruption, cyber operations disruption, social technical disruption, human resource issues (due to temporary skill shortages), and maritime supply chain disruption. These in turn have further impacts on Australia including port congestion and disruption of commercial shipping and supply chain operations. Disruption of the Indo-Pacific maritime logistics network can caused by factors other than those mentioned above. These can be competitive responses/interaction between countries or large organisations; disruptive innovation, e.g. Northern Sea Route, and Belt and Road Initiative; geopolitical disruptions; ecological disruptions, e.g. tsunamis, pandemic, climate change; and trade related disruptions. These could have impacts on Australia including disruption of IT systems and trade networks, port and shipping operations, supply chain operations, critical supply shortages, loss of human lives, exhaustion of emergency rescue and security capabilities, economic downturn and social unrest. The second study analyses the vulnerability of the tanker shipping network that Australia relies on for fuel supplies using Auto Identification System data. The analysis result indicates that while Australia’s energy trade with Malaysia, Indonesia, Singapore, the US, Japan, Taiwan (China), Vietnam and the Philippines is not critically exposed to maritime security threats in South China Sea and East China Sea, energy trade of the latter countries is substantially exposed to tanker operations disruption caused by a closure of the South China Sea and East China Sea. All shipping routes connected to Taiwan will be directly impacted and so will all imports to Brunei. Seven out of eight shipping routes to Japan are affected and six of them are subject to a very significant impact. Six out of ten shipping routes to Malaysia, four out of fourteen routes to Singapore, and two out of seven routes to Thailand will be affected. The closure of the South China Sea and East China Sea will force tankers to avoid these seas causing tanker tonnage shortages and disruption of the fuel supply chains. As a result, Australia may join allies and other countries in the region in ensuring the Freedom of Navigation Operations (FONOPS) and upholding the rules-based international maritime order. The third study highlights the vulnerabilities of the Australian maritime industry due to cyber-attacks and analyses the potential impact of cyber attacks on Australian maritime information systems under five cyber security threat scenarios, namely attacks on Australian destined shipping in the Malacca Straits; attacks on Australian bound shipping in the Lombok Strait; attacks on Australian bound